Normal incidence sound absorption coefficient of direct piercing carved wood panels (DPCWP) with geometric pattern - Dimon, Mohamad Ngasri (Faculty of Electrical Engineering, 2008)
Direct piercing carved wood panels (DPCWP) have been used as part of the wall panel for mosques in this country. Among the earliest used of DPCWP is as in Masjid Sultan Zainal Abidin in 1700s, Kuala Terengganu, Terengganu. Among the most recent used of the DPCWP in modern mosque is as in Masjid Putrajaya, Putrajaya, Wilayah Persekutuan. In the case of Masjid Sultan Zainal Abidin, it is envisage, the use of DPCWP is to help in achieving good speech intelligibility inside. This is considering DPCWP allowing sound waves to pass through, hence sound reflection to the main prayer is contain. Minimizing sound reflection toward the mosque main area, ensuring optimization of speech intelligibility. However the use of DPCWP with geometric pattern in Masjid Putrajaya is foresee mainly due to esthetic consideration. This is considering wood carving is among the identity for Malay architecture. The property of DPCWP to allow sound waves to pass through qualifies DPCWP as sound absorber material. This as Sabine, Kutruff and Maekawa definition of sound absorption coefficient. In this research work, the DPCWP with various geometric patterns in the region of 25% to 40% perforation ratio was investigated. Numerical experiments were conducted using Boundary Element Method (BEM). The measured results were obtained using sound intensity measurements technique. Analysis results of sound absorption coefficient for both techniques were discussed using graph and table arrangement. Analysis of resonance frequencies due to types and sizes of apertures in relation to sound absorption coefficient also be highlighted. The measured and numerical results suggest, DPCWP with geometric patterns indeed able to act as good sound absorber. This finding allows DPCWP to be used as sound absorber more effectively in future mosque construction.